2011
DOI: 10.1097/prs.0b013e318230c939
|View full text |Cite
|
Sign up to set email alerts
|

Face Lift

Abstract: The ability to surgically rejuvenate the aging face has progressed in parallel with plastic surgeons' understanding of facial anatomy. In turn, a more clear explanation now exists for the visible changes seen in the aging face. This article and its associated video content review the current understanding of facial anatomy as it relates to facial aging. The standard face-lift techniques are explained and their various features, both good and bad, are reviewed. The objective is for surgeons to make a better aes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 0 publications
0
47
0
1
Order By: Relevance
“…Each offers its set of advantages and disadvantages [3][4][5] and each provides good rejuvenation when properly executed; compared side by side, it is in fact difficult to demonstrate superiority of 1 procedure over the other. [4][5][6][7] A study evaluating the midface elevation using the traditional deep plane versus the transtemporal subperiosteal technique demonstrated that the subperiosteal approach could achieve 43.2% greater elevation of the midface. 1,8 It is, however, technically demanding 1 and associated with a prolonged downtime and higher potential complications.…”
mentioning
confidence: 99%
“…Each offers its set of advantages and disadvantages [3][4][5] and each provides good rejuvenation when properly executed; compared side by side, it is in fact difficult to demonstrate superiority of 1 procedure over the other. [4][5][6][7] A study evaluating the midface elevation using the traditional deep plane versus the transtemporal subperiosteal technique demonstrated that the subperiosteal approach could achieve 43.2% greater elevation of the midface. 1,8 It is, however, technically demanding 1 and associated with a prolonged downtime and higher potential complications.…”
mentioning
confidence: 99%
“…The ascending buccal trunk ramifications run through the fibers outside the anterior border of the masseter in some patients but within the border in others, about 2-3 cm above the mandibular margin. The PMS has been described as being free of facial nerves [17,29]; therefore, the anatomical landmark of the safe zone was thought to be the anterior sub-SMAS dissection (P-Point) recorded anatomically; the distance from the anterior masseter border to the P-Point (X axis) and the distance from the mandibular margin to the P-Point (Y axis) were measured and recorded Buccal branches of facial nerves…”
Section: Discussionmentioning
confidence: 99%
“…Mendelson et al [17] focused on the fact that the SMAS is separated with difficulty from the parotid capsule, whereas it is separated with less difficulty from the masseter fascia because there is an areolar tissue layer between the cheek SMAS and the masseter fascia that makes sub-SMAS dissection easier. They named this areolar cleavage plane overlying the lower masseter the ''premasseter space'' (PMS), studied the detailed anatomy of the PMS, and carried out partial sub-SMAS dissection limited to the PMS [17,29]. Their anatomical study demonstrated that because the PMS is free of nerves, dissection of this area can decrease the risk of facial nerve injury in sub-SMAS dissection [17,29].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations